On the Cyclicality and Stability of Real Earnings - Robert A. Hart; James R. Malley (Institute for the Study of Labor (IZA), 1999)
We show in this paper that important insights into the cyclical behaviour of wages can be gained by dividing (real) average hourly earnings into their straight-time hourly wage and overtime components. Our motivation is based on the idea of employment-contingent contracts. BLS published and unpublished statistics are used to decompose average earnings into (i) the straight-time wage rate, (ii) the ?mark-up? needed to achieve an overtime worker?s earnings rate, and (iii) the proportion of workers working overtime. Using monthly manufacturing data from 1962?1997, cyclicality measures of these components are based on contemporaneous bivariate correlations using four alternative detrending methods while stability is examined using recursive estimation and testing methods. While the wage rate is generally acyclical and unstable, the other two components are highly pro-cyclical and relatively stable.
Keywords: J41; J3; 330; Cyclical behaviour of wages; straight-time wages; overtime; overtime premium; Lohnstruktur; Überstunden; Leistungsorientierte Vergütung; Konjunktur; Schätzung; USA